Fifty eight-year old-patient with acute weight loss, jaundice and pruritis (clinical case) - A. S. Kovalenko; A. F. Sheptulina; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.